ANALISIS KEMAMPUAN PEMAHAMAN DAN PEMECAHAN MASALAH MATEMATIK SISWA SMP PADA MATERI PERSAMAAN LINEAR SATU VARIABEL - Lestari, Kameswari Sri; Nurjanah, Siti; Zanthy, Luvy Sylviana (IKIP Siliwangi, 2019)
This study aims to determine students' mathematical understanding and problem solving abilities in the material of One Variable Linear Equation (PLSV). This research was conducted in the odd semester of the 2018/2019 academic year in Bandung. The population in this study were all students of class VII SMP Negeri 36 Bandung with a total sample of 30 students namely class VII-E. The research instrument used was in the form of six tests of comprehension ability and three test questions for mathematical problem solving abilities. The research method used is qualitative research. Based on the results of the study it can be concluded that errors in understanding and solving mathematical problems of junior high school students are classified as low and there is a relationship between the ability to understand and mathematical problem solving abilities.